A method for preparing ultra-thin conformal epidermal electrode based on micro-nano metal
Through the ultra-thin conformal skin electrode preparation method based on micro-nano metal, the problems of insufficient comfort, signal-to-noise ratio and robustness of the existing electrocardiogram detection electrode are solved, and the electrocardiogram detection effect with high signal-to-noise ratio, high robustness and high comfort are achieved.
Patent Information
- Application Number
- CN202411023786.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-29
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2044-07-29
AI Technical Summary
The existing electrocardiogram detection electrodes have problems such as large size, rigidity, discomfort, low signal-to-noise ratio, poor robustness, and poor breathability, making it difficult to achieve wearable electrocardiogram sensing with high signal-to-noise ratio, high robustness and high comfort.
Using the ultra-thin conformal epidermal electrode preparation method based on micro-nano metal, an ultra-thin electrode is formed by printing a water-soluble polymer solution, a micro-nano metal conductive ink and an adhesion elastic polymer layer, and the electrode is transferred to the skin through a water-soluble release layer to achieve conformal adhesion.
The electrocardiogram detection with high signal-to-noise ratio, high robustness and high comfort is achieved, which reduces the contact impedance, improves the strain insensitivity and breathability of the electrode, and enhances the reliability of the preparation process.
Smart Images

Figure HDA0004967993760000011 
Figure HDA0004967993760000012 
Figure HDA0004967993760000021
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of epidermal electrodes, and in particular to a method for preparing an ultra-thin conformal epidermal electrode based on micro-nano metals. Background Art
[0002] ECG detection is one of the important means of health diagnosis in the current medical field. In the process of ECG signal acquisition, electrodes are the basic devices for capturing and analyzing signals, and the quality of electrodes directly affects the quality of ECG signals. Common physiological electrodes include electrode clips, stainless steel balls, Ag / AgCl gel electrodes, needle electrodes, fabric electrodes, PI electrodes, etc.
[0003] Among them, the metal clip and stainless steel ball are relatively large and rigid, and are uncomfortable to wear, making it difficult to achieve wearable ECG sensing. The needle electrode will pierce the human skin, which can cause harm to the human body.
[0004] Ag / AgCl gel electrodes and PI electrodes are common commercial and medical electrodes, but they have many limitations. For example, the gel in the Ag / AgCl gel electrode has poor conductivity, resulting in a large impedance at the electrode-skin interface, which is not conducive to the acquisition of bioelectric signals with a high signal-to-noise ratio. Millimeter-thick gels are difficult to adhere closely to the skin, so the signal is easily interfered by motion artifacts. In addition, during long-term wearing, the gel may fail due to water loss or sweat accumulation, and the poor air permeability of the electrode itself can easily cause skin irritation or allergies.
[0005] With the rise of flexible electronic technology, elastic epidermal electrodes have received great attention in the past few years. With the emergence of novel materials and structures, the performance of elastic epidermal electrodes has been continuously optimized, and it is expected to replace Ag / AgCl gel electrodes and be commercialized and medicalized in the future.
[0006] There are two main components of the elastic epidermal electrode:
[0007] Stretchable conductors and elastic substrates:
[0008] Researchers at home and abroad are committed to selecting new materials and designing ingenious structures to achieve the "three highs" performance of elastic epidermal electrodes: high signal-to-noise ratio, high robustness and high comfort. The "three highs" performance are not independent of each other, but have a mutually reinforcing relationship.
[0009] First, by reducing the modulus and thickness and improving the adhesion to the skin, the electrode can be effectively conformed to the skin, resulting in lower contact impedance and higher signal-to-noise ratio. At the same time, the close fit between the electrode and the skin makes it less likely to fall off during long-term use, improving robustness. Electrodes with a modulus that matches the skin (<1MPa) also help users wear comfortably.
[0010] Secondly, electrodes with high stretchability can adapt to various deformations of the skin and are not prone to breakage, and maintain a consistent contact surface with the skin, which can accurately collect high-quality and high-resolution physiological signals.
[0011] Finally, since sweat at the electrode-skin interface can cause skin inflammation and increased contact impedance, electrodes with good breathability can effectively evaporate water and moisture while improving monitoring stability and long-term wearability.
[0012] Therefore, the present invention proposes a method for preparing an ultra-thin conformal epidermal electrode based on micro-nano metal. Summary of the invention
[0013] In order to make up for the deficiencies of the prior art and solve the technical problems existing in the background technology, the present invention proposes a method for preparing an ultra-thin conformal epidermal electrode based on micro-nano metals.
[0014] The present invention is achieved through the following technical solutions:
[0015] A method for preparing an ultra-thin conformal epidermal electrode based on micro-nano metal comprises the following steps (eg Figure 1 ):
[0016] Step 1: coating a water-soluble polymer solution on the printed surface of the paper surface which is soaked and used to release the electrode, and after drying, the surface is covered with a water-soluble release layer to obtain a water-release paper with a flat printed surface;
[0017] Step 2: uniformly mix the rheological thickener and the micro-nano metal dispersion to obtain a micro-nano metal conductive ink, and print it on the water-soluble release layer of the water-release paper obtained in step 1, and then sinter the micro-nano metal to obtain a patterned micro-nano metal conductive layer;
[0018] Step 3: coating an adhesive elastic polymer onto the micro-nano metal conductive layer obtained in step 2 through a dot matrix barrier mask, and curing the polymer at room temperature or under heating conditions after leveling to form an adhesive elastic base layer to obtain an ultra-thin electrode;
[0019] Step 4: Paste the electrode side of the ultra-thin electrode obtained in step 3 on the skin surface, wet the back of the water-release paper, dissolve the water-soluble release layer and release the electrode, and after peeling off the paper surface, the electrode is transferred to the skin, thereby preparing an ultra-thin conformal epidermal electrode on the skin.
[0020] Preferably, the paper surface in step 1 is one of glossy paper, transfer paper, coated paper and film paper, which can be soaked and used for transfer.
[0021] Specifically: choose glossy paper for water-soluble polymers.
[0022] Preferably, the water-soluble polymer in the water-soluble polymer solution in step 1 includes one or more of polyvinyl alcohol, polyacrylic acid, polyethyleneimine, polyvinyl pyrrolidone, polyacrylamide, sodium alginate, sodium carboxymethyl cellulose, and dextran.
[0023] Specifically: the water-soluble polymer is polyvinyl alcohol:
[0024] When the water molecules in the polyvinyl alcohol solution evaporate, the molecular forces between the polymer chains are strengthened, allowing them to self-organize into a continuous and flat polymer film structure.
[0025] When this membrane structure encounters water, the long chains formed by the polymerization of vinyl alcohol units can form hydrogen bonds with water molecules, causing the membrane structure to dissolve.
[0026] Preferably, the rheological thickener in step 2 includes one or more of hydroxypropyl methylcellulose, hydroxymethyl cellulose, polyethylene glycol, carboxymethyl cellulose methyl ether, montmorillonite, and nano silica gel;
[0027] Specifically: the rheological thickener is hydroxypropyl methylcellulose (HPMC)
[0028] Preferably, the micro-nano metal in the micro-nano metal dispersion includes one or more of metal nanowires, metal nanosheets, metal nanoparticles, and liquid metal.
[0029] Specifically: the micro-nano metal dispersion liquid is a silver nanowire dispersion liquid;
[0030] The mass fraction of the silver nanowire dispersion is 1-20%, the mass fraction of the hydroxypropyl methylcellulose solution is 1-5%, and the mass ratio of the hydroxypropyl methylcellulose solution to the silver nanowire dispersion is 4:1-1:4.
[0031] Preferably, the mask coating method includes one or more of screen printing, metal mask printing, inkjet printing, letterpress printing, gravure printing, and flexographic printing.
[0032] Specifically, screen printing is selected for printing, and the specific steps of the micro-nano metal conductive layer are as follows:
[0033] Take 100-500μL of micro-nano metal conductive ink, drop it on one side of the screen, and then use a scraper to scrape the ink across the screen pattern at a uniform speed. The ink is printed through the hollow part of the screen onto the water-soluble release layer of the glossy paper to obtain a micro-nano metal conductive layer.
[0034] Preferably, the adhesive elastic polymer is one of modified polydimethylsiloxane (PDMS), polyurethane, gelatin, methacrylated gelatin, polyacrylate, styrene-butadiene-styrene block copolymer, polystyrene-ethylene / butadiene-polystyrene block copolymer, and styrene-isoprene-styrene block copolymer.
[0035] Specifically, screen printing is selected for mask coating, and modified PDMS is selected for adhesive elastic polymer.
[0036] PDMS, a curing agent, and a surfactant are mixed and stirred evenly in a mass ratio of 10:1:0.05-10:1:0.5, and degassed in a vacuum box for 0.5-2 hours to obtain a modified PDMS precursor.
[0037] Take 0.1-2 mL of modified PDMS precursor and drop it on one side of the screen, then use a scraper to scrape the precursor across the screen pattern at a uniform speed, and the precursor is printed onto the micro-nano metal conductive layer through the hollow part of the screen.
[0038] After the modified PDMS is cross-linked and cured at 60-80°C for 2-3h, a non-completely cross-linked polymer base layer is formed due to the inhibitory effect of the surfactant on the cross-linking reaction, which has good flexibility, stretchability and adhesion.
[0039] The beneficial effects of the present invention are:
[0040] 1. The present invention adopts ultraviolet welding or plasma welding technology ( Figure 2 ), reduce the contact resistance between micro-nano metals and improve the strain insensitivity of epidermal electrodes.
[0041] 2. The present invention further flattens the paper surface by coating the water-soluble release layer, which can significantly improve the printing quality and transfer integrity of micro-nano metals and enhance the reliability of the preparation process ( Figure 3 ); The printing base of commercial transfer paper or tattoo paper is a layer of water-insoluble plastic film, so after the electrode is transferred to the skin, its surface is electrically insulated and cannot form a conductive path with the outside world.
[0042] 3. The present invention can conveniently and quickly transfer the epidermal electrode to the surface of various target adherends by simply dissolving the water-soluble release layer and peeling off the paper surface.
[0043] 4. The present invention modifies the polymer substrate so that the electrode is conformally attached to the skin surface, and an ultra-thin polymer substrate or a breathable porous polymer substrate is prepared by coating with a dot matrix barrier mask with a specific pore size and spacing ( Figure 4 ). BRIEF DESCRIPTION OF THE DRAWINGS
[0044] Figure 1It is a process schematic diagram of the present invention;
[0045] Figure 2 Schematic diagram of the present invention using ultraviolet light source and plasma to weld AgNWs;
[0046] Among them, a means that the AgNWs were welded without using UV light source; b means that the AgNWs were welded without using plasma;
[0047] c shows the welding of AgNWs using ultraviolet light source; d shows the welding of AgNWs using plasma;
[0048] Figure 3 The optical microscope images and scanning electron microscope images of the glossy paper surface before and after the flattening treatment of the present invention;
[0049] Wherein, a is an optical microscope image of the glossy paper surface before flattening treatment, and b is an optical microscope image of the glossy paper surface after flattening treatment;
[0050] Figure 4 Schematic diagram of the modified PDMS substrate in the present invention;
[0051] Among them, a, b, and c are optical microscope images of the porous and breathable modified PDMS substrate prepared by the present invention, and d is a physical image of the breathable porous epidermal electrode prepared by the present invention;
[0052] Figure 5 The relative resistance change-strain curves of the present invention using PDMS and modified PDMS as the elastic substrate of the epidermal electrode respectively;
[0053] Figure 6 A physical picture of the functionalized ultra-thin conformal epidermal electrodes with different patterns prepared by the present invention;
[0054] Among them, a is a high-precision patterned electrode transferred on the fingerprint of the finger, b is a high-precision patterned electrode transferred on the back of the hand, c is a strain sensor transferred on the skin of the finger joint, and d is a pulse sensor transferred on the epidermis of the radial artery;
[0055] Figure 7 A diagram of the epidermal ECG electrodes transferred to the chest for the present invention;
[0056] Figure 8 The present invention provides a high signal-to-noise ratio electrocardiogram monitoring chart with electrodes up to 30 hours. DETAILED DESCRIPTION
[0057] The present invention will be further described below in conjunction with specific examples. It should be understood that these examples are only used to illustrate the present invention and are not intended to limit the scope of the present invention. The experimental methods in the following examples without specifying specific conditions are usually carried out under conventional conditions or under conditions recommended by the manufacturer.
[0058] Unless otherwise defined, all professional and scientific terms used herein have the same meanings as those familiar to those skilled in the art. The reagents or raw materials used in the present invention can be purchased through conventional channels. Unless otherwise specified, the reagents or raw materials used in the present invention are used in a conventional manner in the art or in accordance with the product instructions. In addition, any method and material similar to or equivalent to the described content can be applied to the method of the present invention. The present invention is further described according to the accompanying drawings and specific embodiments of the present invention, and the preferred implementation methods and materials described in the present invention are only for demonstration purposes.
[0059] Embodiment 1:
[0060] Prepare a PVA solution with a mass fraction of 1-5%, and stir it magnetically at 70-95°C for 1-2 hours to obtain a water-soluble polymer solution. Take the printing surface of the glossy paper and immerse it in the PVA solution prepared in the first step, put it in a constant temperature and humidity box and dry it for 7-9 hours at 30-50°C and 5-20% rh. Let the PVA solution dry to form a film as a water-soluble release layer covering the printing surface of the glossy paper, and obtain a water-release paper with a flat surface, such as Figure 3 shown.
[0061] Prepare a HPMC solution with a mass fraction of 1-5%, and magnetically force it at 50-70°C for 1-2 days to obtain a rheological thickener. Mix diphenyliodonium nitrate (DPIN) powder, acetone and deionized water in a mass ratio of 0.01:1:1-0.05:1:1, and mix them evenly on a vortex oscillator to obtain a DPIN solution. Mix the rheological thickener, DPIN solution and AgNWs dispersion in a mass ratio of 1:1:1, and mix them evenly on a vortex oscillator to obtain AgNWs ink. Use a screen plate to print the obtained AgNWs ink on a water-soluble release layer of glossy paper to obtain an AgNWs conductive layer, and place the AgNWs conductive layer under an ultraviolet light source for exposure treatment, such as Figure 2 (a, b). The light power density of the ultraviolet light source is 20-200mW / cm 2 The exposure time is 5-15 minutes. The exposed sample is placed on a heating table for heating treatment, wherein the temperature of the heating table is set to 120-140°C and the heating time is 2-5 minutes.
[0062] PDMS, curing agent and surfactant were mixed and stirred at a mass ratio of 10:1:0.05-10:1:0.5, and then placed in a vacuum box for degassing for 1-3 hours until there were no bubbles. The resulting PDMS solution was coated onto the AgNWs conductive layer through a dot matrix barrier screen with a smaller pore size and a larger spacing. After leveling for 3-6 hours, it was cross-linked and cured on a heating table at 60-80°C for 1-3 hours to obtain an ultra-thin electrode.
[0063] The obtained ultrathin electrode is attached to the skin surface, the back of the water-release paper is moistened with water, the water-soluble release layer is dissolved and the electrode is released, and after peeling off the water-release paper, the electrode is transferred to the skin, thereby preparing an ultrathin conformal epidermal electrode on the skin.
[0064] Embodiment 2:
[0065] Prepare a PVA solution with a mass fraction of 1-5%, and stir it magnetically at 70-95°C for 1-2 hours to obtain a water-soluble polymer solution. Take the printing surface of the glossy paper and immerse it in the PVA solution prepared in the first step, put it in a constant temperature and humidity box and dry it for 7-9 hours at 30-50°C and 5-20% rh. Let the PVA solution dry to form a film as a water-soluble release layer covering the printing surface of the glossy paper, and obtain a water-release paper with a flat printing surface, such as Figure 3 shown.
[0066] Prepare a 1-5% HPMC solution and magnetically hydrate it at 50-70°C for 1-2 days to obtain a rheological thickener. Mix the rheological thickener with the AgNWs dispersion at a mass ratio of 1:1 and mix them evenly by vortex oscillator to obtain an AgNWs ink. Use a screen plate to print the obtained AgNWs ink on the water-soluble release layer of water-release paper to obtain an AgNWs conductive layer. Place the AgNWs conductive layer in a plasma cleaning machine for plasma treatment, such as Figure 2 (c, d). The power is set to 50-70%, and the processing time is set to 60-120s. The treated sample is placed on a heating table for heating treatment, wherein the heating table temperature is set to 120-140°C, and the heating time is 2-5min.
[0067] PDMS, curing agent and surfactant were mixed and stirred at a mass ratio of 10:1:0.05-10:1:0.5, and then placed in a vacuum box for degassing for 1-3 hours until there were no bubbles. The resulting PDMS solution was coated onto the AgNWs conductive layer through a dot matrix barrier screen with a smaller pore size and a larger spacing. After leveling for 3-6 hours, it was cross-linked and cured on a heating table at 60-80°C for 1-3 hours to obtain an ultra-thin electrode.
[0068] The obtained ultrathin electrode is attached to the skin surface, the back of the water-release paper is moistened with water, the water-soluble release layer is dissolved and the electrode is released, and after peeling off the water-release paper, the electrode is transferred to the skin, thereby preparing an ultrathin conformal epidermal electrode on the skin.
[0069] Embodiment three:
[0070] Prepare a PVA solution with a mass fraction of 1-5%, and stir it magnetically at 70-95°C for 1-2 hours to obtain a water-soluble polymer solution. Take the printing surface of the glossy paper and immerse it in the PVA solution prepared in the first step, put it in a constant temperature and humidity box and dry it for 7-9 hours at 30-50°C and 5-20% rh. Let the PVA solution dry to form a film as a water-soluble release layer covering the printing surface of the glossy paper, and obtain a water-release paper with a flat printing surface, such as Figure 3 shown.
[0071] Prepare a 1-5% HPMC solution and magnetically hydrate it at 50-70°C for 1-2 days to obtain a rheological thickener. Mix diphenyliodonium nitrate (DPIN) powder, acetone and deionized water in a mass ratio of 0.01:1:1-0.05:1:1 and mix them evenly on a vortex oscillator to obtain a DPIN solution. Mix the rheological thickener, DPIN solution and AgNWs dispersion in a mass ratio of 1:1:1 and mix them evenly on a vortex oscillator to obtain an AgNWs ink. Expose the AgNWs conductive layer under a UV light source, such as Figure 2 (a, b). The light power density of the ultraviolet light source is 20-200mW / cm 2 The exposure time is 5-15 minutes. The exposed sample is placed on a heating table for heating treatment, wherein the temperature of the heating table is set to 120-140°C and the heating time is 2-5 minutes.
[0072] PDMS, curing agent and surfactant were mixed and stirred at a mass ratio of 10:1:0.05-10:1:0.5, and then placed in a vacuum box for degassing for 1-3 hours until there were no bubbles. The obtained PDMS solution was coated on the AgNWs conductive layer through a dot matrix barrier screen with a larger pore size and a smaller spacing. After leveling for 1-2 hours, it was cross-linked and cured on a heating table at 60-80°C for 1-3 hours to obtain a porous ultra-thin electrode, such as Figure 4 shown.
[0073] The obtained porous ultrathin electrode is attached to the skin surface, the back of the water-release paper is moistened with water, the water-soluble release layer is dissolved and the epidermal electrode is released, and the electrode is transferred to the skin after the water-release paper is peeled off, thereby preparing a porous ultrathin conformal epidermal electrode with good air permeability on the skin, such as Figure 4 shown.
[0074] Embodiment 4:
[0075] Prepare a PVA solution with a mass fraction of 1-5%, and stir it magnetically at 70-95°C for 1-2 hours to obtain a water-soluble polymer solution. Take the printing surface of the glossy paper and immerse it in the PVA solution prepared in the first step, put it in a constant temperature and humidity box and dry it for 7-9 hours at 30-50°C and 5-20% rh. Let the PVA solution dry to form a film as a water-soluble release layer covering the printing surface of the glossy paper, and obtain a water-release paper with a flat printing surface, such as Figure 3 shown.
[0076] The polyvinyl pyrrolidone powder and n-hexanol are mixed in a mass ratio of 1:15-1:25, and heated in a water bath at 60°C for 12-24 hours to obtain a rheological thickener. The rheological thickener is mixed with liquid metal in a ratio of 3g:1mL and subjected to ultrasonic treatment to obtain liquid metal ink. The treatment power is 20-50% and the time is 1-5 minutes. The obtained liquid metal ink is printed on the water-soluble release layer of water-release paper using a screen plate to obtain a liquid metal conductive layer, such as Figure 2 shown.
[0077] PDMS, curing agent and surfactant are mixed and stirred at a mass ratio of 10:1:0.05-10:1:0.5, and then placed in a vacuum box for degassing for 1-3 hours until there are no bubbles. The obtained PDMS solution is coated on the liquid metal conductive layer through a dot matrix barrier screen with a smaller pore size and a larger spacing. After leveling for 3-6 hours, it is cross-linked and cured on a heating table at 60-80°C for 1-3 hours to obtain an ultra-thin electrode.
[0078] The obtained ultrathin electrode is attached to the skin surface, the back of the water-release paper is moistened with water, the water-soluble release layer is dissolved and the electrode is released, and after peeling off the water-release paper, the electrode is transferred to the skin, thereby preparing an ultrathin conformal epidermal electrode on the skin.
[0079] Embodiment five:
[0080] Prepare a PVA solution with a mass fraction of 1-5%, and stir it magnetically at 70-95°C for 1-2 hours to obtain a water-soluble polymer solution. Take the printing surface of the glossy paper and immerse it in the PVA solution prepared in the first step, put it in a constant temperature and humidity box and dry it for 7-9 hours at 30-50°C and 5-20% rh. Let the PVA solution dry to form a film as a water-soluble release layer covering the printing surface of the glossy paper, and obtain a water-release paper with a flat printing surface, such as Figure 3 shown.
[0081] Prepare a HPMC solution with a mass fraction of 1-5%, and magnetically force it at 50-70°C for 1-2 days to obtain a rheological thickener. Mix diphenyliodonium nitrate (DPIN) powder, acetone and deionized water in a mass ratio of 0.01:1:1-0.05:1:1, and mix them evenly on a vortex oscillator to obtain a DPIN solution. Mix the rheological thickener, DPIN solution and AgNWs dispersion in a mass ratio of 1:1:1, and mix them evenly on a vortex oscillator to obtain AgNWs ink. Use a screen plate with different patterns to print the obtained AgNWs ink on the water-soluble release layer of water-release paper to obtain an AgNWs conductive layer. Place the AgNWs conductive layer under a UV light source for exposure treatment, such as Figure 2 (a, b). The light power density of the ultraviolet light source is 20-200mW / cm 2 The exposure time is 5-15 minutes. The exposed sample is placed on a heating table for heating treatment, wherein the temperature of the heating table is set to 120-140°C and the heating time is 2-5 minutes.
[0082] PDMS, curing agent and surfactant were mixed and stirred at a mass ratio of 10:1:0.05-10:1:0.5, and then placed in a vacuum box for degassing for 1-3 hours until there were no bubbles. The resulting PDMS solution was coated onto the AgNWs conductive layer through a dot matrix barrier screen with a smaller pore size and a larger spacing. After leveling for 3-6 hours, it was cross-linked and cured on a heating table at 60-80°C for 1-3 hours to obtain an ultra-thin electrode.
[0083] The obtained ultrathin electrode is attached to the skin surface, the back of the water-release paper is wetted with water, the water-soluble release layer is dissolved and the electrode is released, and the electrode is transferred to the skin after peeling off the water-release paper, thereby preparing functional ultrathin conformal epidermal electrodes with different patterns on the skin, such as Figure 6 shown.
[0084] Embodiment six:
[0085] Prepare a PVA solution with a mass fraction of 1-5%, and stir it magnetically at 70-95°C for 1-2 hours to obtain a water-soluble polymer solution. Take the printing surface of the glossy paper and immerse it in the PVA solution prepared in the first step, put it in a constant temperature and humidity box and dry it for 7-9 hours at 30-50°C and 5-20% rh. Let the PVA solution dry to form a film as a water-soluble release layer covering the printing surface of the glossy paper, and obtain a water-release paper with a flat printing surface, such as Figure 3 shown.
[0086] Prepare a HPMC solution with a mass fraction of 1-5%, and magnetically force it at 50-70°C for 1-2 days to obtain a rheological thickener. Mix diphenyliodonium nitrate (DPIN) powder, acetone and deionized water in a mass ratio of 0.01:1:1-0.05:1:1, and mix them evenly on a vortex oscillator to obtain a DPIN solution. Mix the rheological thickener, DPIN solution and AgNWs dispersion in a mass ratio of 1:1:1, and mix them evenly on a vortex oscillator to obtain AgNWs ink. Use a screen plate with an ECG electrode pattern to print the obtained AgNWs ink on the water-soluble release layer of water-release paper to obtain an AgNWs conductive layer. Place the AgNWs conductive layer under a UV light source for exposure treatment, such as Figure 2 (a, b). The light power density of the ultraviolet light source is 20-200mW / cm 2 The exposure time is 5-15 minutes. The exposed sample is placed on a heating table for heating treatment, wherein the temperature of the heating table is set to 120-140°C and the heating time is 2-5 minutes.
[0087] PDMS, curing agent and surfactant were mixed and stirred at a mass ratio of 10:1:0.05-10:1:0.5, and then placed in a vacuum box for degassing for 1-3 hours until there were no bubbles. The resulting PDMS solution was coated onto the AgNWs conductive layer through a dot matrix barrier screen with a smaller pore size and a larger spacing. After leveling for 3-6 hours, it was cross-linked and cured on a heating table at 60-80°C for 1-3 hours to obtain an ultra-thin electrode.
[0088] The obtained ultra-thin electrode is attached to the skin surface, the back of the water-release paper is moistened with water, the water-soluble release layer is dissolved and the electrode is released, and the electrode is transferred to the skin after the water-release paper is peeled off, thereby preparing an ultra-thin conformal ECG electrode on the skin ( Figure 7 ), can achieve up to 30h of high signal-to-noise ratio ECG detection, such as Figure 8 shown.
[0089] Any matters not described in the present invention are applicable to the prior art.
Claims
1. A method for preparing an ultra-thin conformal epidermal electrode based on micro-nano metal, characterized in that: The following steps are involved: Step 1: coating a water-soluble polymer solution on the printed surface of the paper surface which is soaked and used to release the electrode, and after drying, the surface is covered with a water-soluble release layer to obtain a water-release paper with a flat printed surface; Step 2: uniformly mix the rheological thickener and the micro-nano metal dispersion to obtain a micro-nano metal conductive ink, and print it on the water-soluble release layer of the water-release paper obtained in step 1, and then sinter the micro-nano metal to obtain a patterned micro-nano metal conductive layer; Step 3: coating an adhesive elastic polymer onto the micro-nano metal conductive layer obtained in step 2 through a dot matrix barrier mask, and curing the polymer at room temperature or under heating conditions after leveling to form an adhesive elastic base layer to obtain an ultra-thin electrode; Step 4: Paste the electrode side of the ultra-thin electrode obtained in step 3 on the skin surface, wet the back of the water-release paper, dissolve the water-soluble release layer and release the electrode, and after peeling off the paper surface, the electrode is transferred to the skin, thereby preparing an ultra-thin conformal epidermal electrode on the skin; The adhesive elastic polymer in step 3 is one of modified polydimethylsiloxane, polyurethane, gelatin, methacrylated gelatin, polyacrylate, styrene-butadiene-styrene block copolymer, polystyrene-ethylene / butadiene-polystyrene block copolymer, and styrene-isoprene-styrene block copolymer; By adjusting the pore size and spacing of the lattice barrier described in step three, as well as the time for the adhesive elastic polymer to flow, a completely flat ultra-thin polymer film or an ultra-thin polymer film with a porous morphology can be obtained, thereby achieving the purpose of imparting air permeability to the base layer.
2. The method for preparing an ultra-thin conformal epidermal electrode based on micro-nano metal according to claim 1, characterized in that: The paper surface in step 1 is one of glossy paper, transfer paper, coated paper, and film paper.
3. The method for preparing an ultra-thin conformal epidermal electrode based on micro-nano metal according to claim 1, characterized in that: The water-soluble polymer in the water-soluble polymer solution in step 1 includes one or more of polyvinyl alcohol, polyacrylic acid, polyethyleneimine, polyvinyl pyrrolidone, polyacrylamide, sodium alginate, sodium carboxymethyl cellulose, and dextran.
4. The method for preparing an ultra-thin conformal epidermal electrode based on micro-nano metal according to claim 1, characterized in that: The rheological thickener in step 2 includes one or more of hydroxypropyl methylcellulose, hydroxymethyl cellulose, polyethylene glycol, carboxymethyl cellulose methyl ether, montmorillonite, and nano silica gel.
5. The method for preparing an ultra-thin conformal epidermal electrode based on micro-nano metal according to claim 1, characterized in that: The micro-nano metal in the micro-nano metal dispersion in step 2 includes one or more of metal nanowires, metal nanosheets, metal nanoparticles, and liquid metal; the mass fraction of the micro-nano metal dispersion is 1-20%.
6. The method for preparing an ultra-thin conformal epidermal electrode based on micro-nano metal according to claim 1, characterized in that: The printing or mask coating is one of screen printing, metal mask printing, inkjet printing, letterpress printing, gravure printing, and flexographic printing.
Citation Information
Patent Citations
Method for manufacturing and using wearable flexible skin electrode
CN105326495A
Flexible wearable electrocardio electrode for monitoring cardiovascular diseases and preparation method thereof
CN113460950A